Фантастические рассказы - Саломатов Андрей Васильевич (Школьная библиотека, 2019)
Экземпляры: ф.6 (20190812) / Инвентарный номер: 3151 И / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 16 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-445